The Effect of Product Quality, Online Promotion and Price Perception On Purchase Decisions At Yuwana Printing Sukoharjo - Nur Salim Hari Purnomo; Sri Hartono; Sitti Mukarromah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The purpose of this study is to determine and analyze the effect of product quality, online promotion, and price perception on purchasing decisions at Yuwana Printing, both partially and simultaneously. This study employs a quantitative descriptive research design, with data collected through questionnaires. The data analysis techniques used in this study include multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). Data processing was carried out using SPSS software version 35. The sample consisted of 81 respondents. The results of the study indicate that product quality has a significant effect on purchasing decisions at Yuwana Printing Sukoharjo. Online promotion has a significant effect on purchasing decisions at Yuwana Printing. Price perception also has a significant effect on purchasing decisions at Yuwana Printing Sukoharjo.